Sindroma Bartter pada laki-laki berusia 44 tahun: laporan kasus - Anak Agung Ayu Lydia Prawita; Anak Agung Wiradewi Lestari; Sianny Herawati; Ni Kadek Mulyantari; Ni Komang Krisnawati; Ekarini Katharina Yunarti Nabu (DiscoverSys Inc., 2021)
Background: Bartter's syndrome is a hereditary condition characterized by polyuria, hypokalemia, metabolic alkalosis with normal or slightly low blood pressure due to loss of sodium and renal hyperplasia. Most Bartter syndrome occurs in children and is very rare in adulthood, with a prevalence of 1 in 1,000,000 populations. This case report aims to evaluate the laboratory aspects of Bartter's syndrome in a 44-year-old man at Sanglah Hospital, Bali, Indonesia.Case Presentation: A 44-year-old male patient complaining of vomiting and weakness. Other complaints such as diarrhea, fever, shortness of breath, stiffness and seizures are denied. The patient's previous medical history, treatment history, and family history were denied. Physical examination showed a general weakness with hypotension and polyuria. On laboratory examination, there was severe hypokalemia, hypocalcemia, hypomagnesemia, increased urinary potassium levels, increased urinary chloride levels, and metabolic alkalosis. To differentiate with Gitelman syndrome, an examination of the ratio of urine calcium and creatinine is performed. In this patient, the urine calcium and creatinine ratio increased, which indicated Bartter's syndrome. Patients receive electrolyte replacement therapy.Conclusion: Bartter syndrome is very rare in adulthood. Several tests are needed to make the diagnosis in accordance with the diagnostic approach of hypokalemia, namely electrolyte examination in urine serum, urine creatinine, and blood gas analysis. Latar Belakang: Sindroma Bartter merupakan suatu kondisi herediter yang ditandai oleh poliuria, hipokalemia, metabolik alkalosis dengan tekanan darah normal atau sedikit rendah karena kehilangan natrium dan hiperplasia ginjal. Sebagian besar sindroma Bartter terjadi pada anak-anak dan sangat jarang terjadi pada usia dewasa dengan prevalensi 1 dalam 1.000.000 populasi. Laporan kasus ini bertujuan untuk mengevaluasi aspek laboratorium sindroma Bartter pada laki-laki berusia 44 tahun di RSUP Sanglah, Bali, Indonesia.Presentasi Kasus: Pasien laki-laki 44 tahun dengan keluhan muntah dan lemas. Keluhan lain seperti diare, demam, sesak nafas, kaku dan kejang tidak ada. Riwayat penyakit sebelumnya, riwayat pengobatan, dan riwayat penyakit pada keluarga disangkal pasien. Pada pemeriksaan fisik didapatkan keadaan umum lemah dengan hipotensi dan poliuria. Pada pemeriksaan laboratorium ditemukan hipokalemia berat, hipokalsemia, hipomagnesemia, peningkatan kadar kalium urine, peningkatan kadar klorida urine, dan alkalosis metabolik. Untuk membedakan dengan sindroma Gitelman dilakukan pemeriksaan rasio kalsium dan kreatinin urine. Pada pasien ini didapatkan hasil rasio kalsium dan kreatinin urine yang meningkat, yang mengindikasikan sindroma Bartter. Pasien mendapatkan terapi penggantian elektrolit .Kesimpulan: Sindroma Bartter sangat jarang terjadi pada usia dewasa. Beberapa pemeriksaan diperlukan untuk menegakkan diagnosis sesuai dengan alur pendekatan diagnostik hipokalemia yaitu pemeriksaan elektrolit pada serum urine, kreatinin urine, dan analisis gas darah.